Quirkland - Melkorka Milla Stefánsdóttir 2000- (2024)
The work explores the duality of Iceland: a place where everyday tasks contrast with the surreal and extraordinary. Iceland is a juxtaposition of playfulness and capitalism, advertised as a quirky utopia, an otherworldly paradise. Icelanders capitalize on this image of peculiarity and beauty, using our history and nature as advertising tools. Using ideologies such as Icelanders believing in elves and trolls, women being loose and everyone being a Viking, to bring capital into the country. Is the hypocrisy of our country hidden behind our national brand, and is catering to Iceland’s hyperreality for tourism an appropriate disposition? Í verkinu eru tveir veruleikar Íslands teknir til skoðunnar þar sem hið hversdagslega speglast í hinu súrrealíska og óvenjulega. Við kynnum landið sem undraland, yfirnáttúrulega paradís. Raunveruleikinn er annar. Leikgleði og kapítalismi eru hliðstæðar einingar á Íslandi en er teflt fram í auglýsingarskyni sem sérkennilegri og krúttlegri útópískri eyju í Atlantshafi. Íslendingar hagnast á ímynd landsins um fegurð og furðulegheit. Þeir beita sögu og náttúru landsins sem auglýsingabrellu á alþjóðavísu. Eftir stendur spurningin: Er hræsni þjóðarinnar falin á bak við ímynd landsins, og er fölsuð sjálfsmynd réttmæt leið sem framlag til ferðaþjónustu?